Controlling Horn Beetles Using Pineapple Fruits Trap in Palm Oil Plant - Nasution, Lita; Siregar, Rahmad Syukur; Ginting, Makhrani Sari (Green Engineering Society, 2024)
Chemical insecticides are often used to control palm oil pests due to their effectiveness and rapid effects. However, these insecticides leave residues in palm oil, leading to the presence of harmful chemicals that damage the agricultural environment. This has led to the use of various alternatives, such as mechanical control (trap), which is cost-effective and nature-friendly. Therefore, this study aims to determine the potential of trap with different heights and various amounts of pineapple to control horned beetles in palm oil plant. The study procedures were carried out using a factorial random group design and a factorial scheme with 2 treatment factors and 3 repetitions. The first factor was the height of trap mounted with 3 treatments, namely P1 = 100 cm, P2 = 200 cm, and P3 = 250 cm. Meanwhile, the second factor was N1 = 50 grams per trap, N2 = 100 grams per trap, and N3 = 150 grams per trap. Data obtained were then analyzed using Analysis of Variance. When the results differed, analysis was continued with Duncan's Multiple Range Test at the 5% level. The parameters observed were the number of horn beetles trapped, sex ratio, and the species of horn beetles. The results showed that in height treatment, trap had a significant influence on the number of horn beetles over 3 and 9 days. Meanwhile, in pineapple treatment, weight had no significant effect on the number of horn beetles trapped and sex ratio. The results also showed that the interaction between both treatments had no significant impact.